Integrated SDEC pathway: streamlining specialty reviews from primary care at Basildon University Hospital - Sarah Nafea; Hadeel Bashir; Andrea Barros; Tasmia Farooq; Rafay Khan; Fawad Ali (Future Healthcare Journal)
Introduction: Unnecessary hospital admissions place significant strain on healthcare resources and disrupt patient flow. The Coronavirus 2019 pandemic has exacerbated outpatient backlogs, with routine specialty appointment wait times at Basildon and Thurrock University Hospitals (BTUH) extending to 6–12 months.1–3 Many semi-urgent referrals (ie, those not meeting the urgent 2-week cancer pathway criteria but requiring timely specialist input) often result in hospital admissions due to the lack of an alternative review pathway. To address this, we developed an integrated same-day emergency care (SDEC) pathway, enabling direct specialty reviews in neurology, dermatology and rheumatology for semi-urgent referrals from primary care. This pathway is designed to facilitate timely specialty input for appropriate cases and is not a replacement for routine outpatient clinics. Methods: To determine which specialties would benefit most from SDEC integration, we conducted a retrospective review of GP advice line queries and SDEC call logs at BTUH. Data revealed a high volume of semi-urgent referrals in neurology, dermatology and rheumatology, often leading to unnecessary admissions due to long outpatient wait times.Based on these findings, we collaborated with specialty leads to assess whether these referrals could be managed within SDEC. Although SDEC facilitated triage through strict inclusion criteria, ensuring that only appropriate semi-urgent cases were directed to the pathway, specialty teams agreed to assess these patients within SDEC. Inclusion criteria required patients to be clinically stable (National Early Warning Score (NEWS) score <3) and referred as semi-urgent by a GP. Assessments were conducted by consultants or specialist registrars from the relevant specialty, rather than by acute medical unit clinicians (Fig 1).Over 3 months (2023–2024), we collected data on specialty review volume, waiting times and cost savings to evaluate the effectiveness of the pathway. Results: Implementation of the SDEC pathway led to a 28.4% increase in specialty reviews in 2024 compared with the previous year (Fig 2). The average waiting time was reduced to 1 week, significantly shorter than the standard 3–6-month outpatient wait.4 This prevented unnecessary 24–48-h inpatient stays, because patients received same-day specialist assessment in SDEC. Estimated cost savings totalled £76,145 over 3 months, with projected annual savings of £304,580 (Fig 2). Discussion: This quality improvement pathway demonstrates that structured triage and collaboration between primary and secondary care can significantly improve access to semi-urgent specialty reviews, reducing unnecessary hospital admissions. The selection of neurology, dermatology and rheumatology was data driven, ensuring that the pathway targeted high-demand specialties where delays frequently led to inpatient stays. Crucially, patients were assessed by the appropriate specialty teams within SDEC, ensuring timely and expert input.Strict inclusion criteria maintained appropriate patient selection, preventing system overload.5 Although the initiative has shown success, ongoing evaluation of patient outcomes and resource allocation is essential for long-term sustainability. Future considerations include expanding to additional specialties while ensuring capacity remains manageable. Conclusion: The integrated SDEC pathway effectively facilitates timely specialty reviews in SDEC, reducing outpatient backlogs, preventing unnecessary admissions and generating substantial cost savings.